Whole genome protein microarrays for serum profiling of immunodominant antigens of Bacillus anthracis - Kempsell, Karen E.; Kidd, Stephen; Lewandowski, Kuiama; Elmore, Mike; Charlton, Sue; Yeates, Annemarie; Cuthbertson, Hannah; Hallis, Bassam; Altmann, Daniel; Rogers, Mitch; Wattiau, Pierre; Ingram, Rebecca; et al. (Frontiers in Microbiology, 2015)
A commercial Bacillus anthracis (Anthrax) whole genome protein microarray has been used to identify immunogenic Anthrax proteins using sera from groups of donors with (a) confirmed B. anthracis naturally acquired cutaneous infection, (b) confirmed B. anthracis intravenous drug use-acquired infection (c) occupational exposure in a wool-sorters factory (d) humans and rabbits vaccinated with the UK Anthrax protein vaccine and compared to naïve unexposed controls. Anti-IAP responses were observed for both IgG and IgA in the challenged groups; however the anti-IAP IgG response was more evident in the vaccinated group and the anti-IAP IgA response more evident in the B. anthracis-infected groups. Infected individuals appeared somewhat suppressed for their general IgG response, compared with other challenged groups. Immunogenic protein antigens were identified in all groups, some of which were shared between groups whilst others were specific for individual groups. The toxin proteins were immunodominant in all vaccinated, infected or other challenged groups. However a number of other chromosomally-located and plasmid encoded open reading frames were also recognised by infected or exposed groups in comparison to controls. Some of these antigens e.g. BA4182 are not recognised by vaccinated individuals, suggesting that there are proteins more specifically expressed by live Anthrax spores in vivo and are not currently found in the UK licensed Anthrax Vaccine (AVP). These may perhaps be preferentially expressed during infection and represent expression of alternative pathways in the B. anthracis ‘infectome’. These may make highly attractive candidates for diagnostic and vaccine biomarker development as they may be more specifically associated with the infectious phase of the pathogen. A number of B. anthracis small hypothetical protein targets have been synthesised, tested in mouse immunogenicity studies and validated in parallel using human sera from the same study.